2014
DOI: 10.4028/www.scientific.net/amm.556-562.433
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Properties of Sulfo-Butylated Celluluse Ether (SBC) Based Water-Reducing Agents

Abstract: Abandoned cellulose was treated with acid to prepare Micro-Crystalline Cellulose (MCC) holding affirmative polymerization, which was then treated with 1,4–butanesultone (BS) to synthesize water-soluble Sulfo-Butylated Cellulose ether (SBC). The structure of the SBC was characterized by means of FT-IR, 1H NMR, SEM, and XRD, and its relationship to function was investigated based on the polymerization of MCC and Degree of Substitution (DS). SEM images of hardened cement were also studied. The results indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…There has recently been growing interest in the development of chemically modified polysaccharides as high‐range water reducing admixtures 110 . Numerous investigations have been reported to modify polysaccharides such as starch and pure cellulose for concrete water reducers 6,36,39,57,117–121 . Tegiacchi and Casu 117 found that superplasticizers with superior properties could be produced by sulfonating polysaccharides with suitable sulfonating agents.…”
Section: Bio‐based Concrete Water Reducersmentioning
confidence: 99%
See 4 more Smart Citations
“…There has recently been growing interest in the development of chemically modified polysaccharides as high‐range water reducing admixtures 110 . Numerous investigations have been reported to modify polysaccharides such as starch and pure cellulose for concrete water reducers 6,36,39,57,117–121 . Tegiacchi and Casu 117 found that superplasticizers with superior properties could be produced by sulfonating polysaccharides with suitable sulfonating agents.…”
Section: Bio‐based Concrete Water Reducersmentioning
confidence: 99%
“…This work also demonstrated that starch maleate and starch‐sulfobutyl could be potential substitutes for casein as self‐leveling compounds for concrete. Maimaiti and Aerken 57 investigated the structure and properties of sulfo‐butylated cellulose (SBC) ether for use as water reducing agents in cement paste and concrete. The water‐soluble SBC ether was synthesized by reacting micro‐crystalline cellulose (MCC) and 1,4‐butanesultone (BS) and the product structure was characterized by FTIR, 1H NMR, scanning electron microscopy (SEM) and X‐ray diffraction (XRD).…”
Section: Bio‐based Concrete Water Reducersmentioning
confidence: 99%
See 3 more Smart Citations